2D materials for renewable energy storage devices: Outlook and challenges. Issue 93 (14th September 2016) - Sahoo, Ramkrishna; Pal, Anjali; Pal, Tarasankar
Abstract : We review cost-effective, clean and durable alternative energy devices based on 2D materials. Abstract : Scientists are looking for cost-effective, clean and durable alternative energy devices. Superior charge storage devices can easily meet the demands of our daily needs. In this respect, a material with suitable dimensions for charge storage devices has been considered to be very important. Improved performance of charge storage devices has been derived from whole-body participation and the best are from 2D materials, which provide a viable and acceptable solution.